RSU-coordinated multichannel MAC protocol in vehicular ad hoc network - Caixia SONG; Guozhen TAN; Nan DING (Tongxin xuebao)
A road side unit (RSU)-coordinated multichannel media access control (MAC) (RMM) protocol was proposed in vehicular ad hoc network,which aimed to improve the transmission efficiency of non-safety messages.Under the coordination of RSU,nodes had more opportunities to make SCH reservations on control channel,and the contention-free message transmissions were thus realized.The proposed RMM protocol could use the service channel during the whole synchronization interval for non-safety message transmissions,and thus the saturated network throughput and channel utilization were improved,and the transmission delay was reduced.Compared with other existing protocols,extensive analysis and simulation results demonstrate the superiority of the RMM protocol.